Lymphocytosis after treatment with dasatinib in chronic myeloid leukemia: Effects on response and toxicity. Issue 9 (21st March 2016) - Schiffer, Charles A.; Cortes, Jorge E.; Hochhaus, Andreas; Saglio, Giuseppe; le Coutre, Philipp; Porkka, Kimmo; Mustjoki, Satu; Mohamed, Hesham; Shah, Neil P.
Abstract : BACKGROUND: The proliferation of clonal cytotoxic T‐cells or natural killer cells has been observed after dasatinib treatment in small studies of patients with chronic myeloid leukemia (CML). METHODS: The incidence of lymphocytosis and its association with response, survival, and side effects were assessed in patients from 3 large clinical trials. Overall, 1402 dasatinib‐treated patients with newly diagnosed CML in chronic phase (CML‐CP), CML‐CP refractory/intolerant to imatinib, or with CML in accelerated or myeloid‐blast phase were analyzed. RESULTS: Lymphocytosis developed in 32% to 35% of patients and persisted for >12 months. This was not observed in the patients who received treatment with imatinib. Dasatinib‐treated patients in all stages of CML who developed lymphocytosis were more likely to achieve a complete cytogenetic response, and patients who had CML‐CP with lymphocytosis were more likely to achieve major and deep molecular responses. Progression‐free and overall survival rates were significantly longer in patients with CML‐CP who were refractory to or intolerant of imatinib and had lymphocytosis. Pleural effusions developed more commonly in patients with lymphocytosis. CONCLUSIONS: Overall, lymphocytosis occurred and persisted in many dasatinib‐treated patients in all phases of CML. Its presence was associated with higher response rates, significantly longer response durations, and increased overall survival, suggesting an immunomodulatory effect. Prospective studies are warranted to characterize the functional activity of these cells and to assess whether an immunologic effect against CML is detectable. Cancer 2016;122:1398–1407 . © 2016 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . Abstract : Lymphocytosis develops frequently after treatment of chronic myeloid leukemia with dasatinib and is associated with higher response rates, significantly longer response durations, and increased overall survival. Prospective studies are warranted to assess whether dasatinib produces an immunomodulatory effect against chronic myeloid leukemia.